Performance of Gears Manufactured Through Additive Manufacturing - Animesh Kumar Basak; Jack Ghasseb; Alokesh Pramanik (Metals)
Bound metal deposition (BMD) additive manufacturing technique was used to fabricate gears of PH 17-4 stainless steel material. The gears were fabricated with different layer heights (namely 150 μm and 50 μm) and also subjected to post-fabrication machining. Each gear was tested against commercially available gear in a high-precision control test rig. The operational temperature and noise level were measured during the test, while the material loss due to wear was evaluated at the end of the test. The 50 μm layer height gear performed the best with the least wear loss, minimum noise generation, and temperature rise. The 150 μm layer height gear, which was mechanically polished, performed very similarly to it (50 μm layer height gear) and cost 33% less to print; thus, it was considered the best performing when cost was incorporated. The conclusions found that post machining of printed parts greatly impacts their performance, and thus, the post-print conditions should be considered just as much as the printing conditions.